Strategic Alliance or Hegemonic Strategy? Conservatism Among the Dispossessed. (1st March 2003) - Apple, Michael
This article examines a growing phenomenon—the growth of seemingly conservative sentiments among disenfranchised groups. I take as a prime example of such growth the strategic support of neo-liberal and neo-conservative policies by an African American activist group, the Black Alliance for Educational Options (BAEO). At the core of my analysis is a concern about what is at stake for all of us if rightist multiculturalism succeeds in redefining what and whose knowledge is of most worth and what our social and educational policies are meant to do. I argue that no matter what one's position is on the wisdom of BAEO's strategic actions, the entire case provides a crucial example of the politics of disarticulation and re-articulation, on the ways in which social movements and alliances are formed and re-formed out of the material and ideological conditions of daily life, and of the politics of discursive re-appropriation. Thus, an analysis of such movements is important both in terms of the balance of forces and power involved in specific educational reforms, but also in terms of more general issues concerning the processes of social transformation and agency. A critical but sympathetic understanding of groups such as BAEO may enable us to avoid the essentialism and reductionism that enters into critical sociological work on the role of struggles over state policies. Further, it can provide a more nuanced sense of social actors and the possibilities and limits of strategic alliances in a time of conservative modernization.